A Multidisciplinary Approach for Restoration Ecology of Shallow Coastal Lagoons, a Case Study in South France - De Wit, Rutger; Leruste, Amandine; Le Fur, Ines; Sy, Mariam Maki; Bec, Béatrice; Ouisse, Vincent; Derolez, Valérie; Rey-Valette, Hélène (Frontiers in Ecology and Evolution, 2020)
By the end of the twentieth century, many of the coastal lagoons along the French Mediterranean coast showed insufficient water quality and degraded ecosystem states due to anthropogenic impacts. Among these, nutrient over-enrichment, resulting in eutrophication, has been a major concern. The Water Framework Directive of the E.U. (WFD) has initiated public action to improve their water quality and ecosystem state using an approach rooted in restoration ecology. Here we analyse how this has been applied for the coastal lagoons in South France, considering eutrophication as an example of ecosystem degradation and oligotrophication as the corresponding way for ecological restoration of the eutrophied coastal lagoons. Oligotrophication trajectories, initiated by the reduction of external nutrient loading, have resulted in a quick recovery (i.e. within 3 years) of integrative water column variables (Chlorophyll a, total N and P). The biomass of phytoplankton dropped very quickly showing concomitant changes in their community compositions. Starting from hypertrophic systems, the oligotrophication trajectory is described by a sequence of three ecosystem states dominated respectively by (i) phytoplankton with bare non-vegetated sediments, (ii) opportunistic macroalgae, (iii) angiosperm and perennial macroalgae, punctuated by regime shifts between these ecosystem states. Nevertheless, the latter regime shift has not been observed for the most degraded ecosystems after 10-years oligotrophication. The N and P accumulated in sediments during eutrophication may also retard the ecological restoration. In shallow freshwater lakes, the phytoplankton-dominated and the angiosperm-dominated states are also characteristic for highly-degraded and fully-restored ecosystems states, respectively. In contrast, opportunistic macroalgae do not bloom in these systems. Hence, the multiple stable state model, used successfully for these lakes, cannot be applied straightforwardly for coastal lagoons. To be successful, ecological restoration should consider societal questions as according the DPSIR framework it typically is a response of society. Local citizens and highly-involved stakeholders strongly value the coastal lagoons and attribute very high importance to their regulating ecosystem services (ESs). Different stakeholder profiles are related to different perceptions and appreciations of cultural ESs. Finally, more studies are needed to asses compatibility and incongruencies between the WFD and the Habitats directives, as both apply to coastal lagoons.